Analysis of Export Demand for Indonesian Agricultural Commodities by the Chinese Market - Riyani, Riyani; Darsono, Darsono; Ferichani, Minar (AGRARIS: Journal of Agribusiness and Rural Development Research, 2018)
China is one of the main export destination of Indonesian agricultural commodities. Nevertheless, the export trend of Indonesian agricultural commodities to China during  2012-2016 tend to declined, therefore it is necessary to analyze it. This research aimed to analyze the determinant of Indonesian agricultural commodities export demand by China. Indonesian agricultural commodities export demand was estimated using a regression model on panel data. Panel data in this research consisted of ten data of Indonesian agricultural commodities export to China during 1999-2016 period. The results showed that Indonesian agricultural commodities export demand by China was significantly influenced by real GDP per capita of China, real exchange rate, export price of agricultural commodities and import tariff of agricultural commodities in China.An increasing in real GDP per capita lead an increase in Indonesian agricultural commodities export demand. The depreciation of Rupiah which was expected to increase export demand, but in this research it decreased Indonesian agricultural commodities export demand from China.In addition, Indonesian agricultural commodities export demand tend to increased despite the export prices of agricultural commodities and import tariffs of agricultural commodities in China increased.